Reflective learning through blog reflection among TESL undergraduates - Hon, Isolde Pei Sha; Md Rashid, Juridah; Mukundan, Jayakaran; Alkhatib, Nada (Human Resource Management Academic Research Society, 2020)
Reflective learning (RL), collaborative learning (CL) and project-based learning (PBL) have long been acknowledged as important aspects of personal and professional development. The aim of this study was to identify the reflection dimensions (affective, behaviour and cognition) based on Sage’s ABC-123 Table of Organizing Reflections and the writing stages that were embedded in the learners’ blogs. The sampling for the study was purposeful and the participants were 10 TESL, 3rd year undergraduates. Research data was collected from participants’ reflections through blog entries. In this study, data analysis also included the reading and transcription of blog entries. The findings of the study showed that participants were engaged in the reflection process and produced responses that included all three reflection dimensions within their personal and group blogs. More reflective writing was produced using the initial stages of reflection rather than those which required higher order thinking skills. This study expects to provide ESL instructors with valuable information on how students perceive and experience RL, CL and PBL which are crucial to better equip our students holistically by integrating RL, CL and PBL in their work to allow them to produce quality content even through an online setting.